Models for selecting a rational supply structure of components for uav manufacturing UNDER risk conditions, constrained logistics costs and time limitations - Polupan, Yuriy; Malyeyeva, Olga (INNOVATIVE TECHNOLOGIES AND SCIENTIFIC SOLUTIONS FOR INDUSTRIES, 2025)
The subject of this paper is logistics structures used to ensure the supply of components for the production of unmanned aerial vehicles (UAVs). The goal of the article is to improve the efficiency of supply of components for UAV production through the selection of a rational logistics structure. The following tasks are addressed: to analyze the peculiarities of the formation of the logistic structure of supply of components of the UAV production; to form a set of logistics supply structures options and criteria for their evaluation; and to developement mathematical models for the multicriteria selection of a logistics structure. The methods used include data analysis and generalization, structural variant synthesis and the main criterion method. The following results were obtained according to the objectives. The main types of component elements were generalized for different UAV classes. The analysis of potential component suppliers revealed a variety of choices, which determines the diversity and heterogeneity of possible supply structures. The formation and analysis of the main types of logistics structures made it possible to define a set of criteria for evaluation their advantages and disadvantages. A comparative analysis of various logistics structures of the enterprise is conducted, highlighting their key characteristics based on the main criteria such as minimal risk, cost efficiency, delivery speed, scalability, and flexibility in crisis conditions. A decision tree for the selection of logistics structure, considering the strategic goals of the enterprise (such as minimizing cost, delivery time, or logistics risks), was developed. A generalized multicriteria decision-making problem was formulated using the main criterion method. Three formalized models of the problem of selecting a rational logistics structure were discussed. Conclusions: The results of the study can be applied to improve logistics strategies in the field of UAV manufacturing, particularly in reducing delivery time (according to the established production rhythm) and minimizing risks during wartime conditions. Further research will focus on developing optimization models for combined supply and distribution structures.